2012
DOI: 10.1093/heapol/czs099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of performance-based financing on primary health care services in Haiti

Abstract: To strengthen Haiti's primary health care (PHC) system, the country first piloted performance-based financing (PBF) in 1999 and subsequently expanded the approach to most internationally funded non-government organizations. PBF complements support (training and technical assistance). This study evaluates (a) the separate impact of PBF and international support on PHC's service delivery; (b) the combined impact of PBF and technical assistance on PHC's service delivery; and (c) the costs of PBF implementation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 8 publications
3
26
0
2
Order By: Relevance
“…Indeed, the findings of the study show that health facilities that are on the PBF scheme have higher efficiency score relative to facilities not on the scheme. Zeng et al [26] also provided evidence to confirm the relevance of PBF in health service delivery at the primary level. They found that in Haiti, even modest incentives from PBF schemes were associated with notable growth rates in service delivery.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the findings of the study show that health facilities that are on the PBF scheme have higher efficiency score relative to facilities not on the scheme. Zeng et al [26] also provided evidence to confirm the relevance of PBF in health service delivery at the primary level. They found that in Haiti, even modest incentives from PBF schemes were associated with notable growth rates in service delivery.…”
Section: Discussionmentioning
confidence: 92%
“…Schemes rewarding multiple outcomes differed dramatically in their complexity. Some schemes rewarded just a handful of indicators, for instance a P4P scheme in Haut-Katang in the DRC rewarded seven indicators [45] or a P4P scheme in Haiti rewarded 14 indicators [46]. However, others are extremely complex, a good example is Brazil's national P4P scheme (called PMAQ -National Program for Improving Primary Care Access and Quality), which rewarded over 600 different indicators [47].…”
Section: Design Of P4p Schemes In Lmicsmentioning
confidence: 99%
“…Information on whose performance was measured was provided for all identified P4P schemes and information on who ultimately received the payment was available for 38 out of 41 schemes. Most identified P4P schemes (76%) measured the performance of health institutions such as primary healthcare facilities [46] or hospitals [48]. However, 86% of P4P schemes in LMICs paid financial bonuses to individual providers.…”
Section: Who Is Incentivised?mentioning
confidence: 99%
See 1 more Smart Citation
“…A randomised evaluation of P4P in Rwanda demonstrated a significant increase in maternal and child health services compared to facilities that did not receive performance incentives (Basinga et al, 2011). Another study in Haiti associated performance-based financing with significant improvement in the quantities of primary health care services for infants and pregnant women (Zeng, Cros, Wright, Shepard, 2012). …”
mentioning
confidence: 99%